Analysis of Legal Protection for Victims of Drug Abuse in the Narcotics Research Unit of the Barelang Police, Batam City - Yasral, Alex (UNISSULA Semarang, 2025)
The purpose of the study is to analyze and describe the legal protection of victims of drug abuse in the Narcotics Investigation Unit of the Barelang Police, Batam City based on the perspective of Law Number 35 of 2009 concerning Narcotics and to find out and analyze future criminal law policies in providing legal protection for victims of drug abuse in the Narcotics Investigation Unit of the Barelang Police, Batam City. This type of research is normative legal research with a statutory approach with descriptive-prescriptive characteristics sourced from secondary data, including: primary legal materials and secondary legal materials. This secondary data includes primary legal materials, secondary legal materials and tertiary materials obtained by means of literature study, then analyzed by legal analysis. Based on evidence in the form of witness statements, clues, letters, suspect statements and confiscated evidence, my analysis to answer the formulation of the problem is what form of legal protection is given to perpetrators of drug abuse, namely that the form of legal protection from the police as the suspect's actions can be suspected of committing a crime. In addition, the results of this study show that the form of drug abuse in the Barelang Police Research Unit, Batam City itself is divided into abusers, drug trafficking, drug production and personal prescription abuse for general abuse that occurs in the jurisdiction of the Barelang Police, Batam City itself, namely personal abuse and drug trafficking.